pengaruh harga, kualitas produk, dan kepuasan konsumen terhadap keputusan pembelian pada Thrift store di Instagram - Aulia Rosmaniar; Artia Rahmawati; Rio Riandi; Selly Suci Martasari; Tri Putra Ganesha (Digital Economic, Management and Accounting Knowledge Development (DEMAnD), 2021)
This study aims to examine the effect of price, product quality, and customer satisfaction on purchasing decisions. The object used in this study is the Thrift store on Instagram. The method used in this research is through a survey with a questionnaire instrument. The sample used in this study is the consumer at the Thrift store on Instagram with a total of 72 respondents. Statistical tests were carried out using PLS-based Structural Equation Modeling. The validity test uses the factor loading value, then the reliability test uses the Cronbach'c alpha value, composite reliability and Average Variance Extracted (AVE). After all the results of the indicator items used in this study were valid and reliable, then the hypothesis was tested. The results of the hypothesis test show that the price has positive and significant effect on purchasing decisions with a P-Value (0.001 <0.05), the product quality has positive and significant effect on purchasing decisions with a P-Value (0.003 <0.05). Consumer satisfaction has positive and insignificant effect on purchasing decisions with a P-Value (0.204> 0.05). The conclusion of this study is the importance of maintaining product quality, providing appropriate prices, and ensuring customer satisfaction in order to increase consumers decisions in purchasing.